Politiets brug af peberspray - Garly Andersen & Vedel Kessing, Diverse: (Nordisk Tidsskrift for Kriminalvidenskab, 2016)
English title: Police use of pepper spray This article discusses the use of pepper spray by police since its introduction to Denmark in 2008. Pepper spray contains pepper extract and has been assessed as capable of causing serious health risks by the Danish Health Authority. International human rights bodies have also expressed concerns about the use of pepper spray. Despite this, no comprehensive study or evaluation of the use of pepper spray has ever been conducted in Denmark. The article uses qualitative interviews with police officers and people exposed to pepper spray, as well as a review of reports from police officers about their use of pepper spray, in an examination of whether Danish rules and practices fully comply with human rights requirements and recommendations. The situations in which pepper spray is typically used are described with a focus on where it is used and who it is used against. The authors express concern about the use of pepper spray in a number of situations and argue that its authorization should be more restrictive and precisely regulated. Finally, the article describes a dialogue with the Danish National Police and the pending police act regulating pepper spray.